International & transnational criminal law - Currie, Robert J. (Irwin Law, 2020)
"International criminal law has focused on the prosecution of truly international crimes–genocide, crimes against humanity, war crimes, and aggression. The emerging field of transnational criminal law reflects the fact that our post-Cold War, post-9/11 world has seen the growth of transnational crimes of international concern, such as terrorism, money laundering, organized crime, and human and narcotics trafficking, as well as transnational crimes of domestic concern, which are simply ordinary domestic crimes that involve the jurisdiction of more than one state. This book surveys these two related but increasingly distinct fields with a focus on Canada, bringing together in one accessible text topics that are of increasing importance in a world of globalized crime, from a substantive perspective and through examination of the expanding range of international tribunals dealing with such crimes. This third edition updates caselaw and international practice from Canada, including substantial revisions relating to the prosecution of cross-border crimes. It also combines examinations of international courts and tribunals, transnational criminal law treaties, and recent literature to provide a unique perspective on these two international law disciplines that, while best viewed as separate, retain a common heritage and some overlapping concepts and applications."– Provided by publisher.